Recognition of the shortage of scientific research on sugarcane production in the sugar-energy sector - Silva, Reinaldo Gomes da; Delboni, Clóvis; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2020)
This article developed an analytical scenario referring to the scientific research carried out in the last four years on the subject of sugarcane, with the objective of surveying in which areas the innovations on the subject have been carried out. Regarding the methodological approach, this research is exploratory, descriptive, deductive and a systematic review of the literature was made with bibliometric analysis using the technological resource vosviewer as an instrument to carry out the research. The SCOPUS database component of the Portal of Periodicals for the Coordination and Improvement of Higher Education Personnel (CAPES) was considered. The results found show that the sugarcane theme is worked on and published by the areas of biology, agriculture and botany. The investigation demonstrates an opportunity regarding scientific research work, within the CAPES Portal and in the SCOPUS database, for the area of ​​management and business in the sugar-energy sector. The contribution of research is in the identification of gaps in scientific research, in areas with the greatest opportunities for future studies.
Keywords: Sugarcane; bibliometric analysis; innovation